PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS GENIALLY TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS II UPTD SD INPRES OEBA 4 KOTA KUPANG - Oktovianus, Meriyaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the effect of using Genially-based learning media on the mathematics learning outcomes of class II students at UPTD SD Inpres Oeba 4, Kupang City. The background to this research focuses on the low student learning outcomes caused by the use of conventional learning methods that are less interesting and interactive. This research uses a quantitative method with a One Group Pretest-Posttest Design. The subjects in this research were all 23 class II students at SD Inpres Oeba 4, Kupang City. The instruments used include pretest and posttest data analysis was carried out through descriptive statistical tests and inferential statistics using the SPSS version 23 program. The research results showed a significant increase in student learning outcomes after implementing genially media. The average student pretest score was 44,17, increasing to 73.91 on the posttest. the normality test swows that data is normality distributed. The paired sample t-test obtained a significance value of 0,000 < 0,05. This means that there is a significant difference between learning outcomes before and after treatment. Furthermore, the N-Gain test result show a value of 0,53 which is included in the medium category, with the level of learning effectiveness being in the quite effective category. Ih this way, it ccan be concluded that the use of genially based interactive learning media has a positive influence on students mathematics learning outcomes.